propose concept for mobile learning financial literacy at Malaysian elementary school - Nurul Ain Hidayah; Shamsul Arrieya Ariffin (Pejabat Karang Mengarang UPSI, 2022)
Financial literacy is very important to everyone for survival nowadays. Currently, in Malaysia, there is a problem for students in learning getting a grasp of financial literacy because they are lack of education in finance. They cannot be able to coop or organize themselves even for simple financial transactions or finance skipping. Therefore, in order to solve this problem, we proposed the objectives of this research. First of all, we need to identify the requirement of a suitable mobile application for financial literacy for children. Secondly, we are going to develop an interactive courseware based on financial literacy to help the students to overcome the problem. Thirdly, we are going to evaluate the interactive courseware to know how the level of user satisfaction using our software. So, therefore this study is intended to design and develop mobile learning application interactive courseware for financial literacy for elementary school students. The methodology that used in this mobile learning software development is ADDIE and we use it together with the software development life cycle (SDLC). After that, this research is going to evaluate using heuristic evaluation. The result expected will be the requirement of the criteria design of the software. Secondly, the result expected will be a prototype of software for financial literacy for elementary school students. Therefore, this article proposed a conceptual framework for this study. Then the final result expected is the level of satisfaction the users using the software. Future studies will be conducted to meet the stated objectives.